Neuropsychological Symptom Identification and Classification in the Hospitalized COVID-19 Patients During the First Wave of the Pandemic in a Front-Line Spanish Tertiary Hospital - Molina, Juan D.; Rodrigo Holgado, Irene; Juanes González, Alba; Combarro Ripoll, Carolina Elisa; Lora Pablos, David; Rubio, Gabriel; Alonso, Jordi; Rivas-Clemente, Francisco P. J. (Frontiers in Psychiatry, 2022)
Studies specifically designed to determine the profile of psychiatric symptoms among COVID-19 patients are limited and based on case series, self-report questionnaires, and surveys. The objective of the study was to identify and classify the neuropsychological symptoms of hospitalized COVID-19 patients during the first wave of the pandemic in one of the most important front-line tertiary hospitals from Spain, and to analyze its correlation with diagnosed mental disorders, as well as to explore potential risk factors associated with mental health problems. This observational, cohort study involved data from COVID-19 patients at the University Hospital 12 de Octubre (Madrid, Spain) from February to May 2020. Firstly, patients were undergoing on a semi-structured phone interview (screening phase), based on the Mini International Neuropsychiatric interview (MINI). Then, the confirmation of the diagnosis (confirmation phase) was performed in patients who reported a mental disorder development or worsening. A factorial analysis was performed to identify group of symptoms. A tetrachoric matrix was created and factorial analysis, by a principal component analysis, was employed upon it. Factors showing values >1.0 were selected, and a varimax rotation was applied to these factors. Symptoms most frequently identified in patients were anosmia/ageusia (54.6%), cognitive complaints (50.3%), worry/nervousness (43.8%), slowing-down (36.2%), and sadness (35.4%). Four factors were identified after the screening phase. First (“anxiety/depression”) and second (“executive dysfunction”) factors explained 45.4% and 11.5% of the variance, respectively. Women, age between 50 and 60 years, duration in the hospital (more than 13 days), and psychiatric history showed significant higher levels (number of symptoms) in factors. This study reports the factor structure of the psychiatric symptoms developed by patients with a confirmed diagnosis of SARS-CoV2 during the first wave of the COVID-19. Three items’ domains (anxiety, depression, and post-traumatic stress disorder symptoms) loaded together on one factor, whereas sleep disturbance stood up as a separate factor. Interestingly, the item anosmia/ageusia was not captured by any factor. In conclusion, an increase of neuropsychiatric morbidity is expected in the upcoming months and years. Therefore, screening for early symptoms is the first step to prevent mental health problems associated to this pandemic.